STUDI KUALITATIF KEPUASAN HIDUP PRIA TRANSGENDER (WARIA) DI BANDA ACEH - Ruhghea, Sara; Mirza, Mirza; Rachmatan, Risana (Faculty of Psychology, Diponegoro University, 2014)
Abstract Transgender person is an individual who thinks and feels differently from the assigned gender; it is classified asa gender identity disorder; in this study context is a man who changed himself to be a woman. This uncommonbehavior struggles for social acceptance in Indonesian society due to gender construction debate. This study aimsto assess life satisfaction of male transvestite living in Kota Banda Aceh through understanding on therespondents’ life experiences. A qualitative phenomenological approach was used in this study. Respondentswere collected using the snowball technique. Four men who changed to be women participated in this study.Subject I: 34 years old, has been living as a transgender for 13 years; Subject II: 24 years old, has been living asa transgender for 8 years; Subjek III: 27 years old, has been living as a transgender for 4 years; and Subject IV:36 years old, has been living as a transgender for 12 tahun. The result showed that life satisfaction was achievedwhen subjects accepted their conditions and their success in changing their bodies to be women. Their lifesatisfaction was derived from social support given by other male transvestites and by their partners that fulfilledtheir needs to love and to be loved. The greatest obstacle they encountered was rejection from the society whichincreased their anxiety because they did not fulfilled social expectation to behave in accordance to their gender.They used religious practices to cope with this obstacle. Male transvestite achieved an optimum life satisfactionwhen they are able to accept their lives and receive social support from the society.